Epidemiological profile of the homeless population assisted by voluntary initiative and the social impact on access to healthcare: an investigative study in Curitiba, Brazil - Gomes, Rafael Senff; de Lima Passoni, Luiza Cardoso; Sirigatti, Ricardo; Cavassin, Francelise Bridi (Journal of Community Medicine and Health Solutions, 2021)
Objective: The study aimed to describe the epidemiological profile of the homeless population and report the social impact on healthcare services provided by a voluntary initiative during one-year of follow-up. Method: This is an investigational study, carried out in an important capital-city of southern Brazil, which included 509 individuals in 2019. Findings were divided into three segments: sociodemographic, substance use/abuse and impact on healthcare. Results: The sociodemographic profile found was predominantly male, white, single, heterosexual, educated in elementary or high school, in regular use of legal and/or illegal substances, and living as homeless for less than a year. The impact of assistance provided on the perception of individuals who returned in subsequent actions was evident. Conclusion: The significant increase in the number of homeless people in large urban centers can benefit from the support of non-profit organizations to address the deficiencies faced in accessing basic health services. Based on this, we seek to advance in the development of new policies that improve local healthcare for the vulnerable population, to be more assertive to their needs.